Campur Kode Dalam Web Series Kaget Nikah Karya Vemmy Sagita dan Implikasinya Dalam Pembelajaran Bahasa Indonesia Di SMA - Alicia Margareta; Albertus Purwaka; Patrisia Cuesdeyeni; Petrus Poerwadi; Nirena Ade Christy (Universitas Palangka Raya, 2024)
The general aim of this research is to describe the phenomenon of code-mixing in the dialogue of the main characters of the web series